The Implementation Of Standard Training, Certification And Watchkeeping 2010 To Redesign The Maritime English Syllabus For Fulfilling Students’ Needs - Marselia, Marselia; Hartono, Rudi (Universitas Negeri Semarang, 2017)
Effective communication among seafarers on board between ship to ship or ship to shore is very important in maritime industry concerning the safety at sea. This study aims to evaluate the current ESP syllabus of Maritime English for Nautical Study Program of Politeknik Maritim Negeri Indonesia (Polimarin) Semarang under the requirements of STCW 2010 and based on need analysis which in line with a Competency-Based Syllabus as anticipation of the vision of the Institution to be an international reputable maritime institution.The problems solved in the study were: (1) the implementation of STCW 2010 on the existing syllabus of maritime English for Nautical Study Program of Polimarin, (2) the format of the existing syllabus of Maritime English for Nautical Study, (3) the problems revealed when the existing syllabus is analyzed based on the STCW 2010, and (4) the influence of need analysis to redesign of the existing syllabus.The methodology of this study was the combination between desk and survey study that involved IMO curriculum and 32 respondents (26 students of Nautical Study Program; 4 English lecturers and 2 ex-seafarer for their evaluation on the set of English materials). With triangulation of data sources, the obtained data could get credibility and it was expected to serve for ESP course development.The results of the analysis indicated that the current syllabus has to be improved or, in other words, it should be redesigned in terms of format to be competency-based syllabus. Meanwhile, the survey of students’ competency mapping and preference and needs toward Maritime English showed that the four language skills should be taught in an integrated way, using a package program of ESP for Maritime English Course suitable with the International Convention of STCW 2010, IMO Model Course 7.03 and IMO Model Course 3.17 as issued by IMO. Some suggestions are made related to the syllabus evaluation. Based on the results, it is necessary for the Nautical Study Program to considerredesigning the syllabus of ESP Maritime English. To support teaching and learning process, teaching materials need to be improved, especially related to some textbooks, handbooks and other maritime publications.